Bone-anchored prostheses for transfemoral amputation: a systematic review of outcomes, complications, patient experiences, and cost-effectiveness - Rehani, Mayank; Stafinski, Tania; Round, Jeff; Jones, C. Allyson; Hebert, Jacqueline S. (Frontiers in Rehabilitation Sciences, 2024)
Introduction: Bone-anchored prostheses (BAP) are an advanced reconstructive surgical approach for persons with a transfemoral amputation who are unable to use the conventional socket-suspension systems for their prostheses. Access to this technology has been limited in part due to the lag between the start of a new procedure and the availability of evidence that is required before making decisions about widespread provision. This systematic review presents as a single resource up-to-date information on aspects most relevant to decision makers i.e., clinical efficacy, safety parameters, patient experiences, and health economic outcomes of this technology.A systematic search of the literature was conducted by an information specialist in PubMed, MEDLINE, Embase, CINAHL, Cochrane Library, the Core Collection of Web of Science, CADTH's Grey Matters, and Google Scholar up until May 31, 2023. Peer-reviewed original research articles on outcomes of clinical effectiveness (health-related quality of life, mobility, and prosthesis usage), complications and adverse events, patient experiences, and health economic outcomes were included. The quality of the studies was assessed using the Oxford Centre for Evidence-Based Medicine Levels of Evidence and ROBINS-I, as appropriate.Results: Fifty studies met the inclusion criteria; however, twelve of these were excluded. Thirtyeight studies were finally included in this review. Twenty-one of these studies focused on clinical outcomes and complications. Nine case series and one cohort study were included as they focused specifically on complications and adverse events. Two qualitative studies on patient experience and five on health economic assessments were included. Single arm trials (pre-post intervention design) with varying lengths of follow-up were the most common study design.The clinical efficacy of this technology is evident for selected populations. Overall, patients report increased health-related quality of life, mobility, and prosthesis usage postintervention. The most common complication is a superficial or soft-tissue infection. More serious complications are rare. Patient-reported experiences have generally been positive. Evidence indicates that bone-anchored implants for prosthesis fixation are cost-effective for those who face significant challenges in using socket-suspension systems, although they may offer no additional advantage to those individuals who are functioning well with their socket-suspended prostheses.